PENGARUH PERTUMBUHAN PERUSAHAAN, LEVERANGE, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Riska Dwi Amelia; Dirvi Surya Abbas; Hesty Ervianni Zulaecha; Sigit Budi Santoso (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2022)
This research was conducted to determine the effect of company growth, leverage, profitability, and company size on company value in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2021 period. The study population was 39 manufacturing companies listed on the Indonesia Stock Exchange (IDX) with a study period of 4 years. The sample selection method is purposive sampling and there are 8 companies that match the sample criteria. The data analysis method uses panel data and ordinary least squares (OLS). The results of hypothesis testing show that partially Firm Growth has a negative and significant effect on firm value, Leverage has a negative and significant effect on firm value, Profitability has a negative and significant effect on firm value, and Company Size has a positive and significant effect on firm value. Simultaneously there is a significant influence of company growth, leverage, profitability, company size on firm value.